Tricuspid insufficiency an indirect marker of constriction or premature fetal closure of the ductus arteriosus: report of a case and review of the literature - Tipiani Rodríguez, Oswaldo (2017)
Both fetal ductus arteriosus constriction and closure have an unknown prevalence because most of these cases have no clinical significance, but there is a suspicion that many of them are not detected due to lack of training of the sonographer. We report the case of a pregnant woman who received a dose of metamizole and the fetal echocardiographic examination showed tricuspid regurgitation. We review the association between tricuspid regurgitation and ductus arteriosus patency. The lesson of this case is that the finding of tricuspid regurgitation should prompt evaluation of the ductus arteriosus by a trained person or either opts for referral to a center with more experienced professionals.